Porcine pathogenic Escherichia coli strains differ from human fecal strains in occurrence of bacteriocin types - Bosák, Juraj; Hrala, Matěj; Pirková, Viktória; Micenková, Lenka; Čížek, Alois; Smola, Jiří; Kučerová, Dana; Vacková, Zdenka; Budinská, Eva; Koláčková, Ivana; Šmajs, David (Veterinary microbiology, 2019)
Enterotoxigenic and Shiga-toxigenic Escherichia coli (i.e., ETEC and STEC) are important causative agents of human and animal diseases. In humans, infections range from mild diarrhea to severe life-threating conditions, while infections of piglets result in lower weight gain and higher pig mortality with the accompanying significant economic losses. In this study, frequencies of four phylogenetic groups, fourteen virulence- and thirty bacteriocin determinants were analyzed in a set of 443 fecal E. coli isolates from diseased pigs and compared to a previously characterized set of 1283 human fecal E. coli isolates collected in the same geographical region. In addition, these characteristics were compared among ETEC, STEC, and non-toxigenic porcine E. coli isolates. Phylogenetic group A was prevalent among porcine pathogenic E. coli isolates, whereas the frequency of phylogroup B2, adhesion/invasion (fimA, pap, sfa, afaI, ial, ipaH, and pCVD432) and iron acquisition (aer and iucC) determinants were less frequent compared to human fecal isolates. Additionally, porcine isolates differed from human isolates relative to the spectrum of produced bacteriocins. While human fecal isolates encoded colicins and microcins with a similar prevalence, porcine pathogenic E. coli isolates produced predominantly colicins (94% of isolates); especially colicins B (42.6%), M (40.1%), and Ib (34.0%), which are encoded on large conjugative plasmids. The observed high prevalence of these colicin determinants suggests the importance of large colicinogenic plasmids and/or the importance of colicin production in intestinal inflammatory conditions.
Keywords: železo; průjem; proteiny z Escherichia coli; ETEC; feces; Humans; Iron; Virulence Factors; Colicin; Phylogeny; Enterotoxigenic Escherichia coli; STEC; koliciny; gastrointestinální trakt; Diarrhea; Pig; lidé; symbióza; plazmidy; zvířata; shiga-toxigenní Escherichia coli; Bacterial Adhesion; Escherichia coli Proteins; Intercellular Signaling Peptides and Proteins; faktory virulence; Symbiosis; transportní proteiny; Swine; Feces; Shiga-Toxigenic Escherichia coli; Colicins; Carrier Proteins; enterotoxigenní Escherichia coli; bakteriální adheze; proteiny fimbrií; mezibuněčné signální peptidy a proteiny; fylogeneze; Bacteriocins; polymerázová řetězová reakce; Polymerase Chain Reaction; Bacteriocin; E. coli; Fimbriae Proteins; Animals; Plasmids; Gastrointestinal Tract; prasata; bakteriociny